2024
DOI: 10.1186/s13018-023-04469-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound-guided lumbar plexus and sacral plexus block combined with general anesthesia on the anesthetic efficacy and surgical outcomes in elderly patients undergoing intertrochanteric fracture surgery: a randomized controlled trial

Ji Feng,
Guangyan Tang,
Yunhua Shui
et al.

Abstract: Background Surgery for intertrochanteric fractures in elderly patients is challenging due to the risk of severe pain and significant stress responses. We investigated the effects of a combined approach of ultrasound-guided lumbar plexus and sacral plexus block with general anesthesia on anesthetic efficacy and surgical outcomes in these patients. Methods A randomized controlled trial was conducted involving 150 elderly patients, divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In comparing a single-shot lumbar plexus block as the primary anesthetic to a subarachnoid block, one study showed the lumbar plexus blockade to provide more stable intraoperative hemodynamics and a longer duration of postoperative analgesia in patients undergoing intertrochanteric hip fracture repair [ 35 ]. Even if not used as the primary anesthetic, a lumbar plexus block as an adjunct to general anesthesia compared to general anesthesia alone for hip fracture repair has been shown to improve intraoperative hemodynamics in addition to facilitating lower postoperative pain scores (1, 3, and 6 h), faster recovery times, and the decreased incidence of adverse events [ 36 ]. Although the lumbar plexus block is a great block, due to its level of difficulty and higher complication risks, its utilization has significantly dropped due to the availability of safer alternatives such as the FICB and FNB.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%
“…In comparing a single-shot lumbar plexus block as the primary anesthetic to a subarachnoid block, one study showed the lumbar plexus blockade to provide more stable intraoperative hemodynamics and a longer duration of postoperative analgesia in patients undergoing intertrochanteric hip fracture repair [ 35 ]. Even if not used as the primary anesthetic, a lumbar plexus block as an adjunct to general anesthesia compared to general anesthesia alone for hip fracture repair has been shown to improve intraoperative hemodynamics in addition to facilitating lower postoperative pain scores (1, 3, and 6 h), faster recovery times, and the decreased incidence of adverse events [ 36 ]. Although the lumbar plexus block is a great block, due to its level of difficulty and higher complication risks, its utilization has significantly dropped due to the availability of safer alternatives such as the FICB and FNB.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%